2022
DOI: 10.1101/2022.08.01.502333
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma FIB milling for the determination of structures in situ

Abstract: Structural biology inside cells and tissues requires methods able to thin vitrified specimens to electron transparent thicknesses. Until now, focused ions beams based on gallium have been used. However, ion implantation, changes to surface chemistry and an inability to access high currents limit Gallium as an ion beam source. Here, we show that plasma-coupled ion sources can produce cryogenic lamella of vitrified human cells in a robust and automated manner, with quality sufficient for pseudo-atomic structure … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 52 publications
(68 reference statements)
2
13
0
Order By: Relevance
“…For most tiles, the apparent thickness of LSU detections was at least 70 nm less than the estimated sample thickness, indicating that no detections were being made within 35 nm of the lamella edge. It is possible that this is caused by sample damage during FIB-milling as similar values for damaged areas in FIB-milled lamellae have been estimated from sub-tomogram averaging ( Berger et al, 2022 ). This means that LSU detections across the lamellae can be skewed by a change in thickness and sample damage.…”
Section: Resultsmentioning
confidence: 83%
“…For most tiles, the apparent thickness of LSU detections was at least 70 nm less than the estimated sample thickness, indicating that no detections were being made within 35 nm of the lamella edge. It is possible that this is caused by sample damage during FIB-milling as similar values for damaged areas in FIB-milled lamellae have been estimated from sub-tomogram averaging ( Berger et al, 2022 ). This means that LSU detections across the lamellae can be skewed by a change in thickness and sample damage.…”
Section: Resultsmentioning
confidence: 83%
“…These changes are difficult to quantify in terms of damage, and they could in part be caused by other mechanisms such as ice accumulation after milling (23). Argon plasma FIB-damage has been assessed by estimating B-factors of subtomogram averages, comparing averages of particles at less than and greater than 30 nm from the lamella surface, which lacks positional precision (24). The 2DTM SNR represents a more quantitative metric to assess sample integrity.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation will be required. SEM imaging will damage the sample, the highest dose we employed data acquisition with the small pixel size was under 10 -2 e - /Å, lower than the one used during cryo-ET imaging (Berger et al 2022). Though damage increases at the acceleration voltage of SEM due to the increased scattering cross-section, the damage would be expected to be confined to the interaction layer, a depth less than 50 nm.…”
Section: Discussionmentioning
confidence: 99%
“…The use of pFIB to fabricate lamella has been demonstrated with plunge frozen vitrified materials as part of a high-resolution high throughput cryo-ET workflow (Berger et al, 2022). The cryo-ET workflow study indicated that milling with Ar plasma (30kV, 60 pA) beam adversely affected the resolution of sub-tomographically averaged ribosomes to a depth of around 30 nm.…”
Section: Discussionmentioning
confidence: 99%